Manajemen pemasaran: Pengaruh faktor perilaku konsumen dan organisasi terhadap keputusan pembelian pada smartphone xiaomi - Ningrum, Ajeng Rizqi; Nikmah, RA Ulfatun; Rahayu, SE., MM, Dr. Yayuk Sri (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of consumer and organizational behavior in making purchasing decisions. These factors include social, psychological, cultural, and personal factors. Consumer behavior is influenced by interactions with reference groups, family, and the role and social status of the individual. In addition, psychological factors such as motivation, perception, and beliefs also play an important role in shaping consumer purchasing decisions. The research method used is the library research method. Through literature analysis, this study identifies factors in decision making and the dynamics that occur in the organization. The results show that consumer behavior is influenced by social, cultural, and psychological aspects, while organizational behavior is influenced by internal structure and culture. This study aims to provide in-depth insight into the interaction between the two behaviors in the context of modern business.